Estudo de risco de desastres naturais na Vila Medianeira - área urbana de Faxinal do Soturno - RS - Knierin, Igor da Silva (2018)
In urban areas, the process of use and occupation, associated with different socioeconomic factors and the lack of territorial planning, oftentimes, the occupation of areas susceptible to natural processes and characterize areas at risk of natural disasters. This is a recurring problem in Vila Medianeira, located in the urban area of the municipality of Faxinal do Soturno, in the central region of Rio Grande do Sul, Brazil. The study area is characterized by localized urban occupation at the base of a sloping hill and next to a fluvial course of first order, tributary of the river Soturno, factors that make the site susceptible to mass movements and flash floods. Thus, the study aimed to to carry out a risk study of natural disasters in Vila Medianeira. The working methodology consisted of in the literature review, so that they contemplate the state of the art on the subjects hazard and vulnerability, and the creation of two registration form with the definition of degrees (low, medium, high and very high) for the two variables. The risk study, on the other hand, was carried out from the crossing of this cadastral information and allowed the distinction of four degrees of risk: low, medium, high and very high. In total, 70 buildings were registered in Vila Medianeira, 27.15% were in low hazard situation, 25.71% medium hazard, 25.71% high hazard and 21.43% very high hazard. Concerning the vulnerability, 34.28% of the buildings were identified as low vulnerability, 32.86% medium vulnerability, 20% high vulnerability and12.86% very high vulnerability. For the risk it was verified that 35.71% of the buildings are at low risk, 24.29% medium risk, 15.71% high risk and 24.29% very high risk. Based on the data, identified where the risk is present, therefore, necessary actions of management of the risk of natural disasters, either by mitigating the condition of the hazard or the vulnerability of the persons. Finally, this dissertation aims to contribute to the thematic of natural disaster risk based on a methodology of work, as also, with the persons involved in the study area and with a tool that the city hall of Faxinal do Soturno and Civil Defense can use for management of risk of natural disasters in the municipality.